The Role of Strategic Leadership and Absorptive Capacity in Driving Innovation and Business Performance in MSMEs: Evidence from the Indonesian Food and Beverage Sector in West Java - Syahyono, Syahyono; S. Syahyono (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2024)
This study investigates the interplay between strategic leadership, absorptive capacity, business innovation, and business performance in Micro, Small, and Medium Enterprises (MSMEs) within the food and beverage (F&B) sector in West Java, Indonesia. Employing a quantitative approach, the research uses Structural Equation Modeling (SEM) to test hypotheses about the impact of strategic leadership and absorptive capacity on innovation and performance outcomes. The results indicate that strategic leadership influences business performance indirectly, primarily through its role in enhancing absorptive capacity, which, in turn, facilitates innovation. This absorptive capacity is identified as a key driver of business performance in MSMEs. The findings emphasize that effective leadership acts as a catalyst for fostering an environment conducive to learning and innovation, ultimately improving business outcomes. These insights are essential for MSME entrepreneurs and policymakers seeking strategies to enhance innovation and performance, particularly in resource-constrained environments. The study contributes to the theoretical understanding of strategic leadership and absorptive capacity in MSMEs and offers practical recommendations for strengthening business resilience and competitiveness in the rapidly evolving F&B sector.